Influence of Iron on the Structural Evolution of LiNi0.4Fe0.2Mn1.4O4 during Electrochemical Cycling Investigated by in situ Powder Diffraction and Spectroscopic Methods. Issue 15 (5th November 2014) - Yavuz, Murat; Kiziltas‐Yavuz, Nilüfer; Bhaskar, Aiswarya; Scheuermann, Marco; Indris, Sylvio; Fauth, Francois; Knapp, Michael; Ehrenberg, Helmut
Abstract The cathode materials LiNi0.5Mn1.5O4 and LiNi0.4Fe0.2Mn1.4O4 were synthesized using a citric acid‐assisted sol‐gel method with a final calcination temperature of 1000 °C. An impurity phase exists in LiNi0.5Mn1.5O4 powders, which can be eliminated by substituting some of the Ni2+ and Mn4+ ions with Fe3+. The substitution of Fe into the spinel structure was confirmed by NMR and Mössbauer spectroscopy. The initial capacity of LiNi0.4Fe0.2Mn1.4O4 powder synthesized at 1000 °C (LNFMO) is slightly higher than that of LiNi0.5Mn1.5O4 powder synthesized at 1000 °C (LNMO). Additionally, its capacity retention of 92 % at room temperature after 300 cycles at C/2 charging‐discharging rate between 3.5–5.0 V is higher than that of the Fe‐free sample (79.5 %) under same conditions which could arise from the difference in their cycling mechanisms. In order to understand the structural evolution of these materials during electrochemical cycling, in situ studies under real operating conditions were performed. Measurements of initial powders in capillaries and in situ experiments during the first galvanostatic cycle were carried out by high resolution powder diffraction using synchrotron radiation.